- #1
issacnewton
- 1,041
- 37
- Homework Statement
- Prove ##(a+b) + c = a + (b+c)## using Peano postulates
- Relevant Equations
- Peano postulates
I have to prove the associative law for addition ##(a+b) + c = a + (b+c)## using Peano postulates, given that ##a, b, c \in \mathbb{N}##. Now define the set
$$ G = \{ z \in \mathbb{N} |\forall\; x, y \in \mathbb{N} \quad (x + y) + z = x + (y + z) \} $$
Obviously, ## G \subseteq \mathbb{N} ##. Now ## 1 \in \mathbb{N} ## according to Peano postulates. Let ##x, y \in \mathbb{N} ## be arbitrary.
Using the way addition function is defined using the successor function, we have ## (x + y) + 1 = s(x + y) ##. But ##s(x + y) = x + s(y) ## and ## s(y) = y + 1##. So, we have ##(x + y) + 1 = x + s(y) = x + (y + 1)##. This means that ## 1 \in G##.
Now, suppose ##r \in G##. This means that ##r \in \mathbb{N} ## and
$$ \forall\; x, y \in \mathbb{N} \quad (x + y) + r = x + (y + r) $$
Suppose ##x, y \in \mathbb{N} ## be arbitrary. Since, ##r \in G##, we have
$$ (x + y) + r = x + (y + r) $$
$$ \therefore s((x + y) + r) = s( x + (y + r) ) $$
Using definition of addition function, we have
$$ \therefore (x + y) + s(r) = x + s(y + r) = x + (y + s(r)) $$
$$ \therefore (x + y) + s(r) = x + (y + s(r)) $$
From definition of successor function, ## s(r) \in \mathbb{N} ##. Hence ##s(r) \in G##. So, using Peano postulates, ## G = \mathbb{N}##.
Since ##a, b, c \in \mathbb{N}##, we have ## c \in G##. It follows that ##(a+b) + c = a + (b+c)##. Is this proof correct ?
$$ G = \{ z \in \mathbb{N} |\forall\; x, y \in \mathbb{N} \quad (x + y) + z = x + (y + z) \} $$
Obviously, ## G \subseteq \mathbb{N} ##. Now ## 1 \in \mathbb{N} ## according to Peano postulates. Let ##x, y \in \mathbb{N} ## be arbitrary.
Using the way addition function is defined using the successor function, we have ## (x + y) + 1 = s(x + y) ##. But ##s(x + y) = x + s(y) ## and ## s(y) = y + 1##. So, we have ##(x + y) + 1 = x + s(y) = x + (y + 1)##. This means that ## 1 \in G##.
Now, suppose ##r \in G##. This means that ##r \in \mathbb{N} ## and
$$ \forall\; x, y \in \mathbb{N} \quad (x + y) + r = x + (y + r) $$
Suppose ##x, y \in \mathbb{N} ## be arbitrary. Since, ##r \in G##, we have
$$ (x + y) + r = x + (y + r) $$
$$ \therefore s((x + y) + r) = s( x + (y + r) ) $$
Using definition of addition function, we have
$$ \therefore (x + y) + s(r) = x + s(y + r) = x + (y + s(r)) $$
$$ \therefore (x + y) + s(r) = x + (y + s(r)) $$
From definition of successor function, ## s(r) \in \mathbb{N} ##. Hence ##s(r) \in G##. So, using Peano postulates, ## G = \mathbb{N}##.
Since ##a, b, c \in \mathbb{N}##, we have ## c \in G##. It follows that ##(a+b) + c = a + (b+c)##. Is this proof correct ?